Energia eólica, geração de empregos e desenvolvimento sustentável - Simas, Moana; Pacca, Sergio (Estudos Avançados, 2013)
Wind power development in Brazil has experienced a long period of slow growth; however, projects contracted over the last three years might increase the current installed capacity by fivefold. This was the fastest growing clean energy technology over the last decade, bringing environmental and social benefits to several countries. Our work has determined direct and indirect job creation potential due to indigenous wind power deployment. About 195,000 jobs will be created up to 2020, out of which 70% direct, and most of them in construction, which has great local job creation potential. Therefore, wind power plays a major role in the sustainable development of the country.